Pengaruh Citra Merek terhadap Niat Beli Produk Perawatan Kulit Cosrx Konsumen Muslim - Haninah, Asytia; Surur, Miftahus (Universitas Batanghari Jambi, 2025)
The paradigm shift in skincare has undergone a significant transformation—not merely as a functional necessity but also as an expression of identity and cultural pride. Amid globalization and the rise of social media that intensify awareness of personal appearance, the Muslim community has increasingly contributed to shaping beauty trends aligned with their values. This study aims to examine the influence of brand image on the purchase intention of “Cosrx” Korean skincare products among Muslim consumers. A quantitative approach was employed using a survey as the primary data collection method. The results reveal that the brand image of Cosrx significantly and positively affects consumers' purchase intentions. An increase in positive perceptions of the Cosrx brand image is directly correlated with a stronger intention to purchase the product. This finding underscores the importance of strengthening brand image as a strategic effort to enhance consumer interest, particularly within the Muslim market segment. The study offers insights for cosmetic brands seeking to expand their presence in religiously conscious markets by aligning brand values with consumer beliefs and preferences.